Pengembangan Sistem Keamanan Pusat Data dengan Memanfaatkan Group Policy Management - Harahap, Herlina; Handoko, Divi (Jurnal Ilmu Komputer dan Sistem Komputer Terapan (JIKSTRA), 2024)
The increasing development of data communications makes the aspect of data security and confidentiality increasingly important. Information technology is developing very rapidly in human life today, making the need for a centralized data storage system important for storing digital archives and documents. Along with this progress, the need for security on storage media is very necessary because technological progress is directly proportional to the crimes that exist on the internet itself. Therefore, how to build a Data Center security system on a LAN network using Group Policy Management on Windows Server 2012 with the aim of providing Data Center security based on user actions in moving data from client computers to other storage locations. By building this system, users will be able to prevent theft of data on clinet computers. To secure data, it is necessary to have tools that can be used to manage security and several other policies in the Microsoft Windows program. With Active Directory and Group Policy Management in Window Server 2012 it provides an easy and effective way to manage preferences and settings for computers and users. Group Policy Management provides a very simple way to see what's happening within a particular Group Policy Object (GPO). Based on the testing, it can be concluded that the existence of Group Policy Management can improve the data security system so that the data cannot be copied or duplicated and stored in other storage media.